2015
DOI: 10.1002/adfm.201500055
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Stem Cell–Host Immune System Interplay Using Hydrogel Coencapsulation System with an Anti‐Inflammatory Drug

Abstract: The host immune system is known to influence mesenchymal stem cell (MSC)-mediated bone tissue regeneration. However, the therapeutic capacity of hydrogel biomaterial to modulate the interplay between MSCs and T-lymphocytes is unknown. Here it is shown that encapsulating hydrogel affects this interplay when used to encapsulate MSCs for implantation by hindering the penetration of pro-inflammatory cells and/or cytokines, leading to improved viability of the encapsulated MSCs. This combats the effects of the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 56 publications
0
66
0
Order By: Relevance
“…Live imaging and tumor measurements showed that injection of encapsulated hMSCs expressing hemopexin-like proteins adjacent to glioblastoma tumors in nude mice led to a significant reduction in tumor volume (87%) and weight (83%). Alginate hydrogels (elastic modulus ¼ 22 kPa; average pore diameter ¼ 600 nm) have also been shown to augment BM-MSC-mediated bone regeneration by inhibiting the penetration of two pro-inflammatory cytokines, tumor necrosis factor alpha (TNF-a) and interferon gamma (IFN-g) [229]. Consequently, cell apoptosis was significantly decreased.…”
Section: Alginatementioning
confidence: 98%
“…Live imaging and tumor measurements showed that injection of encapsulated hMSCs expressing hemopexin-like proteins adjacent to glioblastoma tumors in nude mice led to a significant reduction in tumor volume (87%) and weight (83%). Alginate hydrogels (elastic modulus ¼ 22 kPa; average pore diameter ¼ 600 nm) have also been shown to augment BM-MSC-mediated bone regeneration by inhibiting the penetration of two pro-inflammatory cytokines, tumor necrosis factor alpha (TNF-a) and interferon gamma (IFN-g) [229]. Consequently, cell apoptosis was significantly decreased.…”
Section: Alginatementioning
confidence: 98%
“…For example, novel biomaterial surfaces [7] , improved immune-instructive biomaterials [8] and incorporated immune modulating cells (e.g. stem cells) [9] could influence the wound healing process. Within the same context, there are several studies in which the phenotype of macrophages inside different 3D biomaterial environment has been studied [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Alginate microspheres can fill the gaps of irregularly shaped defects, enabling minimally invasive surgical procedures. Moshaverinia et al 6567 used alginate hydrogel for the first time as a scaffold for PDLSCs and GMSCs. In their studies, they developed an injectable alginate hydrogel delivery system for PDLSCs and GMSCs.…”
Section: Introductionmentioning
confidence: 99%